PERHITUNGAN HARGA POKOK PENJUALAN DAN PENENTUAN HARGA JUAL PRODUK LEMON SEREH PADA UMKM AJR - Elsa Imelda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
During the Covid-19 pandemic, many SMEs were af ected. The impact is generally in the form of a decrease insales, causing MSMEs to be unable to survive. AJR is one of the MSMEs that has also been af ected by Covid-19.Usually AJR sells fried chicken and other food for lunch for the employees who work in of ice buildings at AJR'sfront of ice. However, since WFH (Work From Home), almost no sales per day except from online orders. The ownerof AJR then tried to make other products that could be sold during the pandemic. Currently, frozen pop chickenproducts, chili sauce and beverage products have been developed. One of the beverage products developed isLemonade and Lemongrass drink. The Lemonade and Lemongrass drink product from AJR is one of the packagingproduct developments during the Covid-19 pandemic. The benefits of Lemonade and Lemongrass can increaseendurance and many other benefits so that it is one of the mainstay products to be promoted which is very useful forpreventing Covid-19. However, there is a problem with this MSME owner, namely determining the selling price inorder to compete with other competitors. The determination of the selling price cannot be separated from how muchthe cost of goods sold is issued. The PKM Untar team helped find the best alternative among various alternativeproduction cost calculations to calculate the cost of goods sold. In addition, the PKM Untar team also helps choosethe right markup price method to determine the selling price so that it can still compete with similar products. ThePKM team also provided a template in the form of Microsoft Excel to enter costs so as to facilitate the calculation ofproduction costs. Finally, the PKM team also provides knowledge about the types of non-production costs if in thefuture there are more and more products produced by AJR so it is necessary to divide the non-production costs. ABSTRAK: Saat pandemi Covid-19, banyak UMKM yang terkena dampak. Dampak umumnya berupa penurunan penjualansehingga menyebabkan UMKM tidak mampu bertahan. AJR merupakan salah satu UMKM yang juga terkenadampak Covid-19. Biasanya AJR menjual ayam goreng dan makanan lainnya untuk makan siang para karyawanyang bekerja di gedung perkantoran di dpn AJR. Namun sejak WFH (Work From Home), nyaris penjualan perharinya hampir tidak ada kecuali dari pesanan online. Pemilik AJR kemudian berusaha membuat produk lainnyayang dapat dijual saat pandemi. Saat ini telah dikembangkan produk ayam pop frozen, sambal dan produk minuman.Salah satu produk minuman yang dikembangkan adalah minuman Lemon Sereh. Produk minuman Lemon Serehdari AJR merupakan salah satu pengembangan produk kemasan di kala pandemi Covid-19 merebak. ManfaatLemon Sereh dapat meningkatkan daya tahan tubuh dan banyak manfaat lainnya sehingga merupakan salah satuproduk andalan untuk dipromosikan sangat bermanfaat untuk mencegah Covid-19. Namun terdapat permasalahanpemilik UMKM ini, yaitu penentuan harga jual agar dapat bersaing dengan pesaing lainnya. Penentuan harga jualtidak terlepas dari berapa harga pokok penjualan yang dikeluarkan. Tim PKM Untar membantu mencarikanalternatif terbaik di antara berbagai alternatif perhitungan biaya produksi untuk menghitung harga pokok penjualan.Selain itu tim PKM Untar juga membantu memilihkan metode harga markup yang tepat untuk menentukan hargajual sehingga masih dapat bersaing dengan produk sejenis. Tim PKM juga memberikan template dalam bentukMicrosoft Excel untuk memasukkan biaya sehingga memudahkan perhitungan biaya produksi. Terakhir tim PKMjuga memberikan pengetahuan mengenai jenis biaya non produksi jika kelak sudah makin banyak produk yangdihasilkan oleh AJR sehingga perlu membagi biaya non produksi tersebut.